EQUIVALENCY OF TRANSLATING PREFIXES FROM JAPANESE INTO INDONESIAN LANGUAGES IN MADO GIWA NO TOTTO – CHAN NOVEL - Fitri, Efit (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2018)
This Research focuses on the prefix translation from Japanese into Indonesian languages in Mado Giwa no Totto - chan novel by Tetsuko Kuroyanagi translated by  Latifah H. Rahmat and Nandang Rahmat. From this study, the writer hopes for finding  formal dan dinamyc equivalencies in the prefix translation processes. Research data were collected from the translated novel. Theories used in this research  are translation equivalency according to Nida and Taber, translation strategy according  Newmark, Vinay dan Darbelnet. The results of the research show that all of the analyzed data possessing dinamyc equivalencies. This is caused by the differences of the language systems between source and target languages, so that the dynamic equivalencies with the transposition method  are more accurate to reach the level of the message naturalness of the source texts. The benefits of the research could be used as additional information and references for anyone who wants to study translation fields, especially for translating prefixes from Japanese into Indonesian languages.